If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + -1b + -3a = 0 Reorder the terms: 5a + -3a + -1b = 0 Combine like terms: 5a + -3a = 2a 2a + -1b = 0 Solving 2a + -1b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. 2a + -1b + b = 0 + b Combine like terms: -1b + b = 0 2a + 0 = 0 + b 2a = 0 + b Remove the zero: 2a = b Divide each side by '2'. a = 0.5b Simplifying a = 0.5b
| (8c+3)(5c-15)=0 | | -x^2+4=-x-2 | | .00012x^2+6=0 | | m^2+5m+2=0 | | 0=c(c+6) | | r^2+8r+25=0 | | -5x=-75 | | m^2+5m-2=0 | | -x^2+3=1 | | 5a-6+4a=3a+18 | | -12+32= | | 0=w(w+6) | | -7p^2-3p=-3p(p-7) | | 50=x+2x+(2x+5) | | 4b+2=3+8b | | -13y=-117 | | -3x=2(x+4) | | -x^2+3=-3x+3 | | x(x-y)-y= | | 3x+2=59 | | x^2-.6667x-2.8889=0 | | 2k-3= | | 2x+2=59 | | 0=-x^2+3 | | -130+3x=113-6x | | -3x+5=x+-5 | | -130+3x=113- 6x | | x^2-2x+6=2x^2-6x-26 | | 9x-83=3x+67 | | 12m^2-32m+20=0 | | X=-x^2+3 | | 7x+5-3x-8=8x+6+5x-9 |